Circulating tumor cells in colorectal cancer – a review of detection methods and clinical relevance - Saadi, Salma; Aarab, Meryem; Tabyaoui, Imane; Jouti, Nadia Tahiri (Contemporary Oncology/Współczesna Onkologia, 2023)
Colorectal cancer (CRC) is the third most common cancer; it is one of the leading malignancies contributing to cancer mortality. Colorectal cancer is the third most diagnosed cancer in men and the second in women worldwide. Diagnosis of CRC depends on several clinical features such as age, primary site, tumor-node-metastasis stage, genetic parameters and the presence or absence of metastasis. The latter is a phenomenon that is induced by the shedding of tumor cells in the blood circulation by the primary tumor. Such cells are known as circulating tumor cells (CTCs). The detection of CTCs is quite challenging due to their scarceness; thus it requires their enrichment and characterization. Studying the utility of CTCs in the diagnosis of CRC has been the aim of several studies; they demonstrated that ≥ 3 CTCs in 7.5 ml of blood is correlated with a worse prognosis and short progression-free and overall survival. Circulating tumor cells have also been monitored to study treatment response and predict future relapses. The present review aims to bring to light the different techniques used to detect and characterize these malignant cells in the peripheral blood of cancer patients as well as the clinical relevance of CTCs in CRC patients.